(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
One of the innovative governance mechanisms in the housing sector of Uzbekistan could be Lean Construction, which is widely discussed in Western literature but still underused in local practice. This study shows that full implementation of Lean principles is limited by local conditions, including weak planning, poor coordination, and lack of internal standards. Therefore, a simplified and practical approach is proposed, based on clear task definition, basic planning, and improved communication. The results suggest that even small changes in daily management practices can significantly improve project efficiency and reduce risks.